Behaviour of Precast Concrete Beam-to-Column Connection with SHS Hidden Corbel Subjected to Monotonic Load - Jen Hua Ling; Jee Hock Lim; Ahmad Baharuddin Abd Rahman (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2021)
Beam-to-column connection is the most critical part of a precast concrete (PC) that governs the integrity of the entire structure, hence its characteristics need to be determined for safe applications in the construction industry. Therefore, this study developed a beam-to-column connection with square hollow section (SHS) hidden corbel. A full-scale test was conducted on eleven T-subframe specimens with various configurations used to investigate the behaviour of the connection under an incremental static load. It was further evaluated using the beam-line method to determine the moment-rotation response and the mechanical properties. Furthermore, this research analyzed the parametric response, the load resisting mechanism, and the feasibility of the connection for PC structures. Due to extensive usage of steel elements, the PC connection gave a higher ultimate strength than the reinforced concrete (RC). Its moment resistance was largely contributed by the hidden corbel embedded in the beam and column, increasing with the column and beam's embedded length. The grout infill prevented the lateral deformation of the hidden corbel and hence strengthened the connection. Due to the low bending resistance of the steel endplate, the PC connection possessed a low stiffness, which led to a larger rotation deformation than the RC connection, and a low design strength. This could be overcome by modifying the shape of the endplate for a higher second moment of inertia in resisting bending. The PC connection was classified as semi-rigid and partial-strength, and only specimen PC-3 was considered feasible for PC structures.